Анна Каренина: роман в 8 частях / комментарии Э. Г. Бабаева] - Толстой Лев Николаевич (1982)
Экземпляры: ф.2 (1982) / Инвентарный номер: 2852 / Цена: 2.30 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Т 53 / ББК: 84(2Рос=Рус)1